Stretchy McHandsome - Schachner, Judith Byron (Dial Books for Young Readers, an imprint of Penguin Random House LLC, New York, 2019)
When Stretchy, a good looking street cat with an unusual personality, takes a break from his large, rambunctious family, he meets Beanie, a girl who is similarly unique.